Generalized Hadamard Fractional Integral Inequalities for Strongly s,m-Convex Functions - Chao Miao; Ghulam Farid; Hafsa Yasmeen; Yanhua Bian (Journal of Mathematics)
This article deals with Hadamard inequalities for strongly s,m-convex functions using generalized Riemann–Liouville fractional integrals. Several generalized fractional versions of the Hadamard inequality are presented; we also provide refinements of many known results which have been published in recent years.